Association of perioperative adverse events with subsequent therapy and overall survival in patients with WHO grade III and IV gliomas - Weber, Lorenz; Padevit, Luis; Müller, Timothy; Velz, Julia; Vasella, Flavio; Voglis, Stefanos; Gramatzki, Dorothee; Weller, Michael; Regli, Luca; Sarnthein, Johannes; Neidert, Marian Christoph (Frontiers in Oncology, 2022)
Background: Maximum-safe-resection followed by chemoradiotherapy as current standard of care for WHO grade III and IV gliomas can be influenced by the occurrence of perioperative adverse events (AE). The aim of this study was to determine the association of AE with the timing and choice of subsequent treatments as well as with overall survival (OS). Methods: Prospectively collected data of 283 adult patients undergoing surgery for WHO grade III and IV gliomas at the University Hospital Zurich between January 2013 and June 2017 were analysed. We assessed basic patient characteristics, KPS, extent of resection, WHO grade, and we classified AE as well as modality, timing of subsequent treatment (delay, interruption or non-initiation) and OS. Results: In 117 patients (41%), an AE was documented between surgery and 3-months follow-up. There was a significant association of AE with an increased time to initiation of subsequent therapy (p=0.005) and a higher rate of interruption (p<0.001) or non-initiation (p<0.001). AE grades correlated with time to initiation of subsequent therapy (p=0.038). AE were associated with shorter OS in univariate analysis (p<0.001). Conclusion: AE are associated with delayed and/or altered subsequent therapy and can therefore limit OS. These data emphasize the importance of safety within the maximum-safe-resection concept.